TO INVESTIGATE THE LIFE QUALITY OF THE PATIENTS WITH DIABETES MELLITUS TYPE 2 COMPLICATED WITH CHRONIC KIDNEY DISEASE - Sadikova N.G; Najmutdinova D.K; Urunbayeva D.A; G`ulomova M.B (Scholar Express Journals, 2023)
The clinical course and quality of life of diabetic nephropathy in patients with chronic kidney disease-induced diabetes Type 2 was studied under the SF-36 survey. For the study, 60 patients with chronic kidney disease were taken for examination. Of these, 40 QD type 2 patients make up core group 1. Control group 2 consisted of 20 SBK-infected non-QD patients. A "SF-36" questionnaire was used to assess quality of life indicators in patients on the examination. According to the SF-36 survey, all indicators are separated into physical and mental components. In patients with chronic kidney disease-complicated diabetes Type 2, there was a decrease in quality of life by the physical component by 23.5% and by the mental component by 16.9% compared to patients with chronic kidney disease who did not have diabetes. Patients with chronic kidney disease as a complication of diabetes mellitus were observed to have more severe SBK compared to non-diabetic patients, and quality of life indicators were found to be dependent on the severity of SBK.
Keywords: diabetes mellitus; diabetic nephropathy; chronic kidney disease